Epidemiology of macrolide-resistant Mycoplasma pneumoniae by age distribution in Japan - Kawakami, Naoki; Namkoong, Ho; Saito, Fumitake; Ishizaki, Masami; Yamazaki, Masahiko; Mitamura, Keiko (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2021)
Mycoplasma pneumoniae (M. pneumoniae) is the major pathogen involved in community-acquired pneumonia in all age groups. Resistance to macrolides, the first-line treatment for M. pneumoniae infection, is a major global public health concern. However, studies evaluating macrolide-resistant M. pneumoniae infection simultaneously in all ages are limited. This study aimed to determine the prevalence and clinical characteristics of macrolide-resistant M. pneumoniae infection in terms of age distribution. We enrolled 292 patients in Tokyo, Japan, who visited Eiju General Hospital or Zama Children's Clinic in 2015–2016. Patients were tested using real-time PCR for M. pneumoniae DNA. PCR-positive patients (n = 151) were further selected and sequentially divided into preschool-aged children (≤5 years, n = 31), school-aged children (6–15 years, n = 101), adolescents (16–19 years, n = 5), and adults (≥20 years, n = 14). We then analyzed the M. pneumoniae infection clinical characteristics, prevalence of macrolide-resistant infection, and 23S rRNA domain V resistance-associated mutation status. We found insignificant differences in the prevalence of macrolide-resistant M. pneumoniae infection among all groups, clinical characteristics, and resistance-associated mutation status in patients with macrolide-resistant M. pneumoniae infection. We also found statistically higher prevalence of mutation-positive (n = 85) M. pneumoniae in patients previously treated with macrolide compared to the mutation-negative group (n = 66); 63.8% vs 11.1% (p < 0.001), respectively. We found no significant differences in both clinical characteristics and prevalence of macrolide-resistant M. pneumoniae infection among all ages. Also, previous macrolide treatment contributes to drug-resistance.